UKURAN PERUSAHAAN, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN MELALUI FINANCIAL DISTRESS - Hikmah, Hikmah; Haldy, Muhammad; Wangdra, Yvonne (LPPM Universitas Putera Batam, 2024)
This research aims to determine the influence of company size, company size and dividend policy on company value with financial distress as a mediating variable. The population in this study are mining companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The total sample tested was 30 companies, multiplied by 5 years of observations selected using purposive sampling techniques. The data analysis technique uses Partial Least Square (PLS) with the SmartPLS 4 program. The research results show that the variables of company size and dividend policy have a positive and significant effect on company value, while profitability has a negative and insignificant effect on company value. Company size, dividend policy have effect on financial distress, while profitability has no significant effect on financial distress, while the effect of financial stress on company value has a negative and significant effect.